2008
DOI: 10.1051/forest:2008021
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition of chestnut litterfall and eight-year soil chemical changes under a no-tillage management system in Northern Portugal

Abstract: -• Chestnut stands (Castanea sativa Mill.) for fruit production, in Northern Portugal, are subjected to frequent soil tillage operations, which is considered a threat for the system sustainability.• The effects of replacement of conventional tillage by the no-tillage system in chestnut stands on decomposition and nutrient dynamics of leaf litter and burs were evaluated, using the litterbag methodology. Amounts of mass and nutrients in the organic layers, and chemical characteristics of the 0-20 cm top soil lay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 26 publications
(36 reference statements)
4
16
0
Order By: Relevance
“…Although the lignin concentration was not considered in our research, the values reported in literature indicate 211 g kg -1 (Sariyildiz, 2008), 246 g kg -1 (Martins et al, 2009) and 272 g kg -1 (Raimundo et al, 2008) for the chestnut leaves. In fact, lignin can dominate litter decomposition rates irrespective of other constituents when the values of initial lignin concentration are higher than 200 g kg -1 (Sariyildiz, 2008).…”
Section: Litterfall Mass Loss and Decomposition Ratesmentioning
confidence: 89%
“…Although the lignin concentration was not considered in our research, the values reported in literature indicate 211 g kg -1 (Sariyildiz, 2008), 246 g kg -1 (Martins et al, 2009) and 272 g kg -1 (Raimundo et al, 2008) for the chestnut leaves. In fact, lignin can dominate litter decomposition rates irrespective of other constituents when the values of initial lignin concentration are higher than 200 g kg -1 (Sariyildiz, 2008).…”
Section: Litterfall Mass Loss and Decomposition Ratesmentioning
confidence: 89%
“…Initial litter chemistry including carbon (C): nitrogen (N) and lignin:N ratios are often correlated with the rate of litter decay and therefore the formation of soil organic matter (Fassnacht and Gower, 1999;Mo et al, 2008;Taylor et al, 1989). Thus, cumulative directional changes in litterfall and litter chemistry can profoundly influence the forest floor properties and therefore its developing trend (Ferrari, 1999;Raimundo et al, 2008). Forest litterfall varies greatly among years (Hennessey et al, 1992;Lin et al, 2003;Wright and Cornejo, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Together with nutrient resorption and foliar leaching (Luyssaert et al 2005), litterfall and subsequent decomposition (Raimundo et al 2008) are major pathways of nutrient return to plants. The relative importance of these pathways is nutrient-specific and can strongly differ between tree species, sites, and age of the trees (Binkley 1986).…”
Section: Introductionmentioning
confidence: 99%